Protocol for a feasibility study of a cohort embedded randomised controlled trial comparing NEphron Sparing Treatment (NEST) for small renal masses. Issue 6 (11th June 2019) - Neves, Joana B; Cullen, David; Grant, Lee; Walkden, Miles; Bandula, Steve; Patki, Prasad; Barod, Ravi; Mumtaz, Faiz; Aitchison, Michael; Pizzo, Elena; Ranieri, Veronica; Williams, Norman; et al.
Abstract : Introduction: Small renal masses (SRMs; ≤4 cm) account for two-thirds of new diagnoses of kidney cancer, the majority of which are incidental findings. The natural history of the SRM seems largely indolent. There is an increasing concern regarding surgical overtreatment and the associated health burden in terms of morbidity and economy. Observational data support the safety and efficacy of percutaneous cryoablation but there is an unmet need for high-quality evidence on non-surgical management options and a head-to-head comparison with standard of care is lacking. Historical interventional trial recruitment difficulties demand novel study conduct approaches. We aim to assess if a novel trial design, the cohort embedded randomised controlled trial (RCT), will enable carrying out such a comparison. Methods and analysis: Single-centre prospective cohort study of adults diagnosed with SRM (n=200) with an open label embedded interventional RCT comparing nephron sparing interventions. Cohort participants will be managed at patient and clinicians' discretion and agree with longitudinal clinical data and biological sample collection, with invitation for trial interventions and participation in comparator control groups. Cohort participants with biopsy-proven renal cell carcinoma eligible for both percutaneous cryoablation and partial nephrectomy will be randomly selected (1:1) and invited to consider percutaneous cryoablation (n=25). The comparator group will be robotic partial nephrectomy (n=25). The primary outcome of this feasibility study is participant recruitment. Qualitative research techniques will assess barriers and recruitment improvement opportunities. Secondary outcomes are participant trial retention, health-related quality of life, treatment complications, blood transfusion rate, intensive care unit admission and renal replacement requirement rates, length of hospital stay, time to return to pre-treatment activities, number of work days lost, and health technologies costs. Ethics and dissemination: Ethical approval has been granted (UK HRA REC 19/EM/0004). Study outputs will be presented and published. Trial registration: ISRCTN18156881 ; Pre-results.